Correcting rotational error in rectal cancer radiation therapy: Can planning target volume margins be safely reduced?. Issue 4 (18th June 2022) - Seah, Vivian; Dundas, Kylie; Hudson, Felicity; Surjan, Yolanda; Bartlett, Rebecca; Ko, Rebecca; Smith, Sandie; Arumugam, Sankar; Johnston, Meredith; Wong, Karen; Lee, Mark
Abstract: Introduction: The magnitude and impact of rotational error is unclear in rectal cancer radiation therapy. This study evaluates rotational errors in rectal cancer patients, and investigates the feasibility of planning target volume (PTV) margin reduction to decrease organs at risk (OAR) irradiation. Methods: In this study, 10 patients with rectal cancer were retrospectively selected. Rotational errors were assessed through image registration of daily cone beam computed tomography (CBCT) and planning CT scans. Two reference treatment plans (TPR ) with PTV margins of 5 mm and 10 mm were generated for each patient. Pre‐determined rotational errors (±1°, ±3°, ±5°) were simulated to produce six manipulated treatment plans (TPM ) from each TPR . Differences in evaluated dose‐volume metrics between TPR and TPM of each rotation were compared using Wilcoxon Signed‐Rank Test. Clinical compliance was investigated for statistically significant dose‐volume metrics. Results: Mean rotational errors in pitch, roll and yaw were −0.72 ± 1.81°, −0.04 ± 1.36° and 0.38 ± 0.96° respectively. Pitch resulted in the largest potential circumferential displacement of clinical target volume (CTV) at 1.42 ± 1.06 mm. Pre‐determined rotational errors resulted in statistically significant differences in CTV, small bowel, femoral heads and iliac crests ( P  < 0.05). Only small bowel and iliac crests failed clinical compliance, with majority in the PTV 10 mm margin group. Conclusion: Rotational errors affected clinical compliance for OAR dose but exerted minimal impact on CTV coverage even with reduced PTV margins. Both PTV margin reduction and rotational correction decreased irradiated volume of OAR. PTV margin reduction to 5 mm is feasible, and rotational corrections are recommended in rectal patients to further minimise OAR irradiation. Abstract : To evaluate the magnitude and resulting impact of rotational error in rectal cancer patients, and to investigate the feasibility of planning target volume (PTV) margin reduction to improve organs‐at‐risk (OAR) sparing.